2021
DOI: 10.1007/s11292-021-09474-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic disparities in violent crime during the COVID-19 lockdown in Miami-Dade County, Florida, 2018–2020

Abstract: Objectives This study uses two cluster detection techniques to identify clusters of violent crime during the 3 months of the 2020 COVID-19 lockdown in Miami-Dade County compared to that during an equivalent period in 2018 and 2019. Methods Violent crime data from the Miami-Dade Central Records Bureau were analyzed. The Local Indicators of Spatial Association statistics and a space‐time permutation statistic were used to identify clusters of violent crimes and outliers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…These results are consistent with the routine activity approach in that depending on how the pandemic changes opportunity structures, different crime types will be affected in different ways. Moise and Piquero ( 2021 ), as with other research, found a decrease in violent crime during the first 3 months of the pandemic in Miami-Dade County, Florida. More interesting, however, is that these authors, using two clustering techniques, found that, consistent with criminological research, prior to the pandemic, largely African American areas with high socio-economic disadvantage had clusters of violent crime.…”
Section: Related Researchsupporting
confidence: 59%
See 1 more Smart Citation
“…These results are consistent with the routine activity approach in that depending on how the pandemic changes opportunity structures, different crime types will be affected in different ways. Moise and Piquero ( 2021 ), as with other research, found a decrease in violent crime during the first 3 months of the pandemic in Miami-Dade County, Florida. More interesting, however, is that these authors, using two clustering techniques, found that, consistent with criminological research, prior to the pandemic, largely African American areas with high socio-economic disadvantage had clusters of violent crime.…”
Section: Related Researchsupporting
confidence: 59%
“…Campedelli et al ( 2020b ) and Moise and Piquero ( 2021 ) are the only known research studies to investigate the impact of COVID-19 on crime at the community, or neighbourhood, level. Considering communities across Chicago, IL, Campedelli et al ( 2020b ) found that predictors varied for their explanatory power of where decreases in crime (burglary, assault, narcotics and robbery) occurred.…”
Section: Related Researchmentioning
confidence: 99%
“…Last, although most of Florida and Miami-Dade County have been open without lockdowns, it will be important to continue to track domestic violence moving forward, especially because people -especially (undocumented) immigrants-continue to feel the pain and anxiety associated with bleak gainful employment prospects and vaccine rollouts. It will also be of interest to explore the potential geographical variability in the patterning of domestic violence in future research, especially because extant research has shown such geographic differences within cities by crime type during the COVID-19 era (Campedelli et al, 2020;Moise & Piquero, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, research has found that arrests for violent crime tend to be concentrated in Black disadvantaged neighborhoods during the pandemic (Moise & Piquero, 2021 ). The disproportionate arrests and mistreatment of racial and ethnic minorities by the criminal justice system is an ongoing problem in the U.S. as well as globally (Toure et al., 2021 ).…”
Section: Differential Vulnerabilities During the Covid‐19 Pandemicmentioning
confidence: 99%